Students’ Perceptions of The Bumper Stickers Strategy in Enhancing Reading Comprehension - Eva Saptarina; Kiki Rizki Amelia; Dewi Sartika (Edu-Ling: Journal of English Education and Linguistics, 2025)
Reading comprehension is essential in English learning, yet many junior high school students struggle to understand descriptive texts because of limited vocabulary, difficulty identifying key ideas, and low engagement. This study investigated students’ perceptions of the Bumper Stickers Strategy as a visual–textual technique to support comprehension. Using a descriptive quantitative survey, data were collected from 40 seventh-grade students of SMP Negeri 1 Kayuagung using an 18-item Likert-scale questionnaire covering perceived effectiveness, engagement, motivation, clarity, and ease of use. Instrument validity was confirmed using Pearson product-moment correlation, and reliability was high (α = 0.84). Descriptive statistical analysis showed a positive overall perception with a mean score of 3.78, indicating that the strategy was effective, clear, easy to use, and helpful in organizing information visually, although engagement and motivation received slightly lower ratings. The findings suggest that the Bumper Stickers Strategy is a beneficial instructional tool for enhancing reading comprehension, supporting cognitive processing, and promoting creative learning, with the potential for broader application in various educational contexts.